PENGARUH TEKANAN KEUANGAN TERHADAP PENGHINDARAN PAJAK - Suprapti, Eny (Jurnal Reviu Akuntansi dan Keuangan)
This study examines the effect of Growth, ROA, Leverage, Cashflow nagatif and size on taxavoidance. The testing was held 82 samples. The data obtained from the company’s annualreport website Indonesian Stock Exchange during the period 2016 and analyzed using MultipleRegresion. The research finding show that ROA negatively affect of tax evaoidance. Other findings indicate leverage positive effect on tax evoidance. ROA is a financial pressure for the company when profitability performance becomes the target that must be achieved and the researchresults show the negative direction, it can be stated that the sample company is not in a state offinancial pressure because the average ROA is lower than the interest rate on deposit. Meanwhile, leverage shows a positive influence on tax evasion. This proves that the sample companies aggressively increased the use of external funding so as to increase tax avoidance.Key words: financial pressure, tax evoidance, triangle fraud theory